Impact of routine Bacillus thuringiensis israelensis (Bti) treatment on the availability of flying insects as prey for aerial feeding predators - Timmermann, Ute; Becker, Norbert (Bulletin of entomological research, 2017)
Since 1980, mosquito breeding habitats in the Upper Rhine Valley were routinely treated with Bacillus thuringiensis var. israelensis (Bti). Bti is considered to significantly reduce the number of mosquitoes, and - especially when used in higher dosages - to be toxic to other Nematocera species, e.g. Chironomidae, which could be food sources for aerial feeding predators. To investigate direct and indirect effects of routine Bti treatment on food sources for aerial feeding predators, the availability of flying insects in treated and untreated areas was compared. A car trap was used for insect collection, which allowed their exact spatiotemporal assignment. The statistical analysis revealed that insect taxa abundance was influenced differently by the factors season, temperature and time of day. Nematocera (Diptera) were the most frequently collected insects in all areas. Chironomidae were the predominant aquatic Nematocera. The comparison of treated and untreated sites did not show significant differences that would indicate any direct or indirect effect of routine Bti treatment on the availability of flying insects. Additional to food availability, food selection must be considered when investigating food resources for aerial feeding predators. In this study, food selection of Delichon urbicum (House Martin) as an example was investigated with the help of neck ring samples. The preferred prey of the investigated D. urbicum colony consisted of diurnal insects with terrestrial larvae (Aphidina, Brachycera, Coleoptera). Chironomidae were consumed, but not preferred.